Demographic Features, Clinical, and Laboratory Findings of Partial and Selective IgA Deficiency in Children - Aslı Arslan; Haluk Çokuğraş; Yıldız Camcıoğlu (Journal of Pediatric Research)
Aim: Immunoglobulin A deficiency (IgAD), which is the most common primary antibody deficiency, can cause clinical problems due to significant infections and associated diseases, while some individuals with IgAD remain symptomless throughout their lives. This study evaluated the demographic features, clinical, and laboratory findings for those patients with selective and partial IgAD. Materials and Methods: A retrospective study was conducted at İstanbul University-Cerrahpaşa, Cerrahpaşa Faculty of Medicine, Clinical Immunology, and Allergy Outpatient Clinic. This study included 149 children, 122 diagnosed with selective and 27 diagnosed with partial IgAD. Results: The median age at diagnosis was 6 years, and the majority of the patients (55.0%) were male. Nine patients transitioned from selective to partial IgAD, while four patients switched from partial to selective IgAD. The majority of patients experienced infections (56.3%) and allergies (47.7%). Autoimmune diseases were present in 14.1% of the study group; thyroiditis was the most common. Immunoglobulin G (IgG) subgroup deficiencies were detected in 20.2% of 84 patients who were examined. B-cell subpopulation analysis was carried out in 22 patients, revealing differentiation abnormalities in 18.1%. Two of these patients were siblings; one had low CD27+IgD-class-switched memory B-cells. Conclusion: This study revealed that infections were the most common concern, but the frequencies of allergic manifestations and autoimmunity were also significant. While studies on B lymphocyte subgroup analysis continue to gain importance, the presence of patients with defects was observed in this study. Following an IgAD diagnosis, patients should undergo close immunological and clinical monitoring.